The changing social worlds of 9-year-olds - Emer Smyth (The Economic and Social Research Institute (ESRI), 2022)
This report compared the experiences of 9-year-olds born a decade apart by drawing on Wave 1 of the Growing Up in Ireland (GUI) Cohort '98, conducted in 2007/08, and Wave 5 of GUI Cohort '08, conducted in 2017/18. It documents changes in their lives across the domains of relationships with family and peers, day-to-day activities and engagement with formal and informal learning. The analyses draw on survey data as well as time-use diaries completed by the children and their families, providing rich insights into their lives against a backdrop of rapid societal transformation. The decade between the two waves, 2007/08 to 2017/18, saw significant economic and social change as well as important policy developments. However, to date little has been known about how these changes have impacted on the lives of children.
Keywords: 330; Kinder; Familienstruktur; Soziale Schicht; Soziale Beziehungen; Freizeitverhalten; Lernen; Irland